The Largest Tubal Pregnancy: 14th Week - Amr Elmoheen; Waleed Salem; Mahmoud Eltawagny; Rehab Elmoheen; Khalid Bashir (Case Reports in Obstetrics and Gynecology)
Subsequent development and implantation of embryo outside the uterine lining are defined as an ectopic pregnancy. Ectopic pregnancies have a wide range of presentations, for example, acute hemoperitoneum to chronic ectopic pregnancy. The case presented is an unusual case of ectopic pregnancy with large hematosalpinx with classic symptoms. To the best of the authors’ knowledge, this case is the largest intact tubal ectopic pregnancy reported ever in the 14th week of gestation. A 40-year-old patient presented to the emergency department with lower abdominal pain, mild dysuria, and loose motion. The patient’s previous menstrual cycles were regular till four months ago, then started to be irregular, and she had no history of chronic diseases except repeated pelvic inflammatory diseases (PID). Clinically, the patient was hemodynamically stable. On palpation, the abdomen was tender, and cervical movements were not tender. BHCG in the blood came very high. The bedside point-of-care ultrasound (POCUS) showed free fluid in the abdomen and a sac in the left adnexa with a living fetus (visible heartbeats). The conventional ultrasound showed 14 weeks of an extrauterine gestational sac with visible early pregnancy. Differential diagnosis was either an abdominal pregnancy versus a complicated tubal pregnancy. The surgical pathology report confirmed the diagnosis of ectopic tubal pregnancy as the tube was dilated in the middle portion containing chorionic villi, decidual reaction, and the whole gestational sac consistent with the ectopic tubal pregnancy. The patient had a successful laparotomy with salpingectomy and hemostasis and did well after the operation. So, an intact ectopic tubal pregnancy may last until the 14th week of gestation.